Customer Involvement-Based Marketing Performance (An Empirical Study on Furniture Industries at Jepara Regency Central Java Province Indonesia) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study is to analyze the customer involvement-based marketing performance focusing on the marketing innovation on customer involvement of export furniture companies in Jepara. This study used quantitative methods. After the research design is made the next step is to determine the population to generalize objects or subjects that have a certain number and characteristics to be determined and used in the study, determine the sample used, and determine the size of the sample, as well as the sampling technique. The next process is to clarify the variables and define the operational variables of the research to understand the variables and types of variables, the indicators of the research variables and the questionnaire design. In the research instrument, the validity test will be carried out to determine the validity of the questionnaire and the reliability test to measure a questionnaire which is an indicator of a variable or construct. The population sample used was 307 furniture export companies. Model testing in the Structural Equation Model (SEM) is carried out with two tests, namely the model fit test and the causality significance test through the regression coefficient test. The results show that marketing innovation has a significant effect on customer involvement. This study shows that the first hypothesis (H1) is accepted. This means that marketing innovation has a significant effect on customer involvement. A good marketing innovation will make customer involvement even better. Marketing innovation contributes directly to customer involvement by 25.8%.